THE TRANSLATING STRATEGIESAPPLIED BY THE FIRST GRADE STUDENTSIN THE TRANSLATION OF A NARRATIVE TEXT: A Case Study at SMA Puragabaya Bandung - HERLINA, - (2009)
The study entitled The Translating Strategies Applied By The First Grade Students In The Translation Of A Narrative Text, A Case Study at SMA Puragabaya Bandung, concerns with the translating strategies which are applied by the first grade students of senior high school in the translation of a narrative text. This study is also to reveal the students' perception towards the translating tasks which are given by their teacher. This study is a qualitative study with using descriptive method. The data is taken from the translation products and the questionnaire results of the ten students as the subject of this study. The data is analyzed through the theory of translating strategies by Peter Newmark (1988). The result shows that the students employ ten translating strategies in dealing with the text. In addition, the students' perception towards the translating tasks is positive; they perceive that the translating tasks help them cultivate their reading habit and vocabulary. Therefore, based on that perception, the translating tasks are still relevant to be applied by the teacher as an alternative task in enhancing the students' reading habit and vocabulary.